(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
The modern education system aims to develop students’ creative communicative abilities through didactic factors, methods, principles, and tools. These factors shape students’ ability to express thoughts, communicate effectively, and solve problems. The educational process should focus on developing students’ creative thinking and communication skills, using multimedia, interactive materials, and online platforms. These didactic factors influence students’ motivation, creative thinking, and communication skills, making them essential for success in any field.